CircRNA Microarray Profiling Reveals hsa_circ_0058493 as a Novel Biomarker for Imatinib-Resistant CML - Zhong, An-Ni; Yin, Yi; Tang, Bing-Jie; Chen, Lei; Shen, Hong-Wei; Tan, Zhi-Ping; Li, Wen-Qun; He, Qun; Sun, Bao; Zhu, Yan; Xiao, Jie; Jiang, Zhi-Ping; et al. (Frontiers in Pharmacology, 2021)
Background: CircRNA has appeared as a critical molecular in the development of various cancers. However, the cellular function of circRNAs and exosomal circRNAs has not been well explored in CML. Methods: Differentially expressed circRNAs were identified by a human circRNA microarray analysis. The expression of hsa_circ_0058493 in monocytes and exosomes was verified using quantitative real-time PCR. Short hairpin RNAs against hsa_circ_0058493 were constructed to silence the expression of circ_0058493. CCK8, flow cytometry and EdU assay were performed to investigate the biological functions of circ_0058493. Results: Hsa_circ_0058493 was significantly overexpressed in the monocytes of CML patients and high level of circ_0058493 was associated with the poor clinical efficacy of imatinib. Silencing the expression of circ_0058493 significantly inhibited the development of imatinib-resistant CML cells. miR-548b-3p was overexpressed in circ_0058493-downregulated CML cells. Bioinformatic analysis revealed that circ_0058493 might exert its regulatory function acting as a “sponge” of miR-548b-3p. Moreover, hsa_circ_0058493 was significantly enriched in the exosomes derived from imatinib-resistant CML cells. Conclusion: Hsa_circ_0058493 is a promising biomarker for CML prognosis and may provide a therapeutic target for CML treatment.